2021
DOI: 10.3389/fbloc.2020.558705
|View full text |Cite
|
Sign up to set email alerts
|

Having Our “Omic” Cake and Eating It Too?: Evaluating User Response to Using Blockchain Technology for Private and Secure Health Data Management and Sharing

Abstract: This paper reports on end users' perspectives on the use of a blockchain solution for private and secure individual “omics” health data management and sharing. This solution is one output of a multidisciplinary project investigating the social, data, and technical issues surrounding application of blockchain technology in the context of personalized healthcare research. The project studies potential ethical, legal, social, and cognitive constraints of self-sovereign healthcare data management and sharing, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A potential benefit of DLT in genomics discussed in the literature is user empowerment . 15 , 21 , 34 DLT allows self-governance of users’ genetic data. 11 , 39 Further, DLT gives users options for consent management.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A potential benefit of DLT in genomics discussed in the literature is user empowerment . 15 , 21 , 34 DLT allows self-governance of users’ genetic data. 11 , 39 Further, DLT gives users options for consent management.…”
Section: Resultsmentioning
confidence: 99%
“…The initial search was conducted in 09/2020 and was updated in 08/2021; overall, resulting in 468 articles. Finally, we identified additional sources through a forward and backward search ( n = 32) on our base literature set, 20 and also manually added one more article to the list of potentially relevant studies (ie, Lemieux et al 21 ) In total, we identified 501 potentially relevant studies.…”
Section: Methodsmentioning
confidence: 99%
“…In academia, discussions on the application of blockchain technology to medical information systems have continued for several years, and most scholars have given positive answers and raised challenges [66], [67], [68], [69]. Asaph Azaria and his colleagues proposed MedRec [40] in 2016, a decentralized record management system using the blockchain technology.…”
Section: Comparison To Other Related Workmentioning
confidence: 99%
“…Recently, solutions based on decentralized identity blockchains have received the attention of some researchers: Belchior et al proposed an SSI-based access control solution, which shows how DIDs and VCs can be integrated with attribute-based access control in a federated setting, minimizing data disclosure and data redundancy; 5 Liu et al proposed an SSI-based solution for multimedia data management; 6 Papadopoulos et al presented a privacy-preserving decentralized workflow that facilitates trusted federated learning among participants; 7 and Lemieux et al proposed a self-sovereign health data management solution, where VCs were used to enable privacy-preserving sharing of personally-identifiable health data. 8 However, the existing solutions do not address the problem of preventing the unauthorized usage of the data after the identity or other data have been shared.…”
Section: Introductionmentioning
confidence: 99%
“…The solution also leverages prior work on self-sovereign health data management, which introduces a privacy preserving and secure solution for self-sovereign data holders to share their health data for research purposes. 8 Thus, we combine the flipped PRIV-DRM model with use of Decentralized Identifiers (DIDs) and Verifiable Credentials (VCs) to establish a self-sovereign oriented distributed trust architecture. We add FHE capabilities to achieve additional privacy protection and data usage control.…”
Section: Introductionmentioning
confidence: 99%